2015
DOI: 10.5056/jnm15091
|View full text |Cite
|
Sign up to set email alerts
|

Colonic Hypersensitivity and Sensitization of Voltage-gated Sodium Channels in Primary Sensory Neurons in Rats with Diabetes

Abstract: Background/AimsPatients with long-standing diabetes often demonstrate intestinal dysfunction and abdominal pain. However, the pathophysiology of abdominal pain in diabetic patients remains elusive. The purpose of study was to determine roles of voltage-gated sodium channels in dorsal root ganglion (DRG) in colonic hypersensitivity of rats with diabetes. MethodsDiabetic models were induced by a single intraperitoneal injection of streptozotocin (STZ; 65 mg/kg) in adult female rats, while the control rats receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
19
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 53 publications
6
19
1
Order By: Relevance
“…Three weeks after STZ injection, ALA at 60 mg/kg or NS in the same volume was injected (IP) once a day for consecutive 7 days. T13-L2 DRGs were dissociated acutely, and small and medium-sized DRG neurons in red were recorded (Figure 2B, arrow), as we have shown in a previous study 15. ALA treatment significantly reduced excitability of colonic DRG neurons, compared with NS.…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations
“…Three weeks after STZ injection, ALA at 60 mg/kg or NS in the same volume was injected (IP) once a day for consecutive 7 days. T13-L2 DRGs were dissociated acutely, and small and medium-sized DRG neurons in red were recorded (Figure 2B, arrow), as we have shown in a previous study 15. ALA treatment significantly reduced excitability of colonic DRG neurons, compared with NS.…”
Section: Resultssupporting
confidence: 71%
“…It was reported that STZ injection led to gastric and colonic hypersensitivity,25,36 in addition to peripheral sensorimotor neuropathy in rats 24,37. Recently, we have reported that diabetic rats display colonic visceral hypersensitivity in response to CRD 15. In the present study, we provided direct evidence for the first time to demonstrate that systematical application of ALA significantly attenuated the colonic visceral hypersensitivity in rats with diabetes.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…3,4,22 In brief, bilateral T9-T13 DRGs were dissected out and incubated in dissecting solution containing collagenase D (1.5-1.8 mg/mL; Roche, Indianapolis, IN, USA) and trypsin (1.2 mg/mL; Sigma-Aldrich) for 90 minutes at 34.5°C. DRGs were then washed and transferred to the dissecting solution containing DNase (0.5 mg/mL; Sigma-Aldrich).…”
Section: Dissociation Of Dorsal Root Ganglion Neuronsmentioning
confidence: 99%